The Efficacy of Calorie-Counting Mobile Applications in Weight Loss: A Comparative Review - Lech, Weronika; Woźniakowska, Iga; Zambrzycka, Maja; Misarko, Aleksandra; Jedwabnik, Monika; Ścigała, Stanisław; Peszuk, Krzysztof; Dobrosielska, Adrianna; Krajewski, Hoang Viet; Olszewski, Bartosz (Quality in Sport, 2026)
Background: Mobile health (mHealth) applications have become the dominant tool for self-monitoring dietary intake. However, their clinical efficacy compared to traditional methods remains a subject of debate. Objective: The aim of this review is to evaluate the efficacy of calorie-counting apps in weight loss, analyzing factors influencing their success, particularly adherence and technological features. Methods: A narrative review was conducted based on a literature search in the PubMed database (2013–2025) using the following query: “(mobile application OR app OR health) AND (calorie counting OR food tracking) AND (weight loss OR weight management)”. The analysis included 23 studies, comprising Randomized Controlled Trials (RCTs) and systematic reviews, to evaluate the clinical efficacy of app-based self-monitoring compared to traditional methods and to assess the impact of user adherence on weight outcomes. Results: Evidence suggests that while apps outperform paper-based methods in the short term (Flores Mateo et al., 2015), their long-term advantage is uncertain without sustained engagement (Metzendorf et al., 2024). Recent trials from 2025 (Bertoli et al., 2025) highlight that "high-adherence" users achieve significant weight loss (-7.0 kg), whereas low engagement leads to negligible results. Conclusions: mHealth technology is a potent facilitator of self-monitoring but not a standalone solution. Efficacy is strictly dose-dependent (frequency of use) and optimized when combined with behavioral support or advanced feedback mechanisms (e.g., biofeedback).